Aplikasi Kompos Titonia dan Limbah Cair Sabut Kelapa Muda Dalam Meningkatkan Pertumbuhan Tanaman Tomat (Lycopersicum esculentum Mill.) - Khusnu Abdillah Siregar; Lufita Nur Alfiah; Al Muzafri; Yuliana Susanti; Edward Bahar (Peneliti.net, 2022)
Application of Titonia Compost and Young Coconut Coir Liquid Waste to Increase Growth and Production of Tomato (Lycopersicum esculentum Mill.) This research was conducted at the Experimental Garden of the Faculty of Agriculture, University of Pasir Pengaraian, Rokan Hulu Regency. The time of this research will be carried out for three months starting from September 2022 to November 2022. The purpose of this research is to determine the main and interaction effect of titonia compost and young coconut coir liquid waste in increasing the growth of stevia plants in a sustainable manner. This study used a factorial completely randomized design (CRD) consisting of two factors. The first factor was titonia compost (T) consisting of 4 levels namely 0, 0.5 kg/plot, 1 kg/plot, 1.5 kg/plot and the second factor was young coconut coir liquid waste (S) consisting of 4 levels namely 0.100 ml/plant, 200 ml/plant, 300 ml/plant to obtain 16 treatment combinations with 3 replications. The parameters observed were harvesting age, number of branches, number of leaves, fresh weight of leaves and dry weight of leaves. The data were analyzed statistically and followed by the Honest Significant Difference Test (SJD) at the 5% level. The results showed that the interaction of Titonia Compost and Young Coconut Coir Liquid Waste was significant for plant height, age of flowering and fruit weight of the plants, and did not give a real response to, harvesting age, number of fruit planted, fruit weight per fruit. The best treatment was found in the combination of Titonia Compost 1.5 kg/plot and Young Coconut Coir Liquid Waste 300 ml/Tan (T3S3). The main effect of titonia compost was significant on all observed parameters with the best treatment dose of 1.5 kg/plot. The main effect of young coconut coir liquid waste is significant on all observation parameters with the best treatment of 300 ml/plant